TPACK Competency Evaluation of Preservice Teachers in Microteaching - Didi Nur Jamaludin; Ani Rusilowati; Edy Cahyono; Sigit Saptono; Aditya Marianti (International Conference on Science, Education, and Technology, 2022)
Technological Pedagogical and Content Knowledge (TPACK) is now recognized for teacher development and preparation programs. The purpose of the study was to evaluate the TPACK competence in microteaching of preservice teachers. The research approach uses qualitative research using the curriculum evaluation design of Stake Countenance Model with data collection including lesson plans, teaching practice activities, performance assessment, and in-depth semi structured interviews. The results of the microteaching evaluation program using an analysis of the ability to integrate pedagogy, content, and technology within the TPACK competency framework. In general, preservice teachers still use technology less, because the lesson plans design dont use learning technology. So for the development of TPACK competencies, preservice teachers provide opportunities for preservice teachers to apply technology in biology learning and use various learning strategies.